Examination of the Leisure Attitudes of Individuals Living in Turkey from an East to West Perspective - Süleyman Munusturlar (Lithuanian Sports University, 2018)
Background. This study aims at examining the leisure attitudes of individuals by comparing eastern and western cities. The study cinvolved 469 individuals who were living within the borders of İstanbul, Ankara, Eskişehir, Van, Tunceli and Hakkari and were selected through convenience sampling. While 257 participants were female, 212 of them were male. Methods. In the study, Independent Samples t-test, which is a parametric test, One Way Variance Analysis (ANOVA) and Kruskal Wallis, which is a non-parametric test, were used in order to determine the independent variables affecting the dependent variable of leisure attitude and its sub-dimensions. Results. The statistical analyses carried out revealed that the city of residence, the region of residence and education had impact on the leisure attitudes. Individuals living in eastern cities had lower leisure attitude scores than those living in western cities, educational status also was an important variable affecting the leisure attitude in eastern cities. Conclusion. In conclusion, leisure attitudes of individuals were affected positively and negatively by many variables within the context of limitations and opportunities that principally the geographical region brings along. Keywords:  leisure, eastern and western cities, leisure participation